Will giving up meat save the environment? - Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
Phil Thornton, of the International Livestock Research Institute (Kenya), and Andy Jarvis, of the International Institute for Tropical Agriculture (Colombia), have both joined a new climate change initiative of the Consultative Group on International Agricultural Research. These two scientists are interviewed at the launch of the new initiative, called 'Climate Change, Agriculture and Food Security'. They describe the importance of livestock livelihoods to one billion of the world's poorest people and caution that before people decide to cut meat from their diets as a way to reduce greenhouse gas emissions, they should consider the impacts of removing livestock from the environment.